2020
DOI: 10.2196/17549
|View full text |Cite
|
Sign up to set email alerts
|

Development and Acceptability of a Tablet-Based App to Support Men to Link to HIV Care: Mixed Methods Approach

Abstract: Background The poor engagement of men with HIV care is attributed to a number of factors: fear of stigma, masculine representations, concerns related to confidentiality, and the time commitment needed to visit public health clinics. Digital technologies are emerging as an approach to support the engagement of men with care. Objective This study aims to deliver a usable and engaging tablet-based app, called EPIC-HIV 2 (Empowering People through Informed … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…Several studies have shown that men are less likely to test for HIV and link to HIV treatment if found to be positive, resulting in poor health outcomes such as unsuppressed viral load and higher AIDS-related death among men [ 5 , 6 , 12 , 17 ]. The recent Test-as-Prevention (TasP) trial conducted in rural South Africa had no significant effect [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown that men are less likely to test for HIV and link to HIV treatment if found to be positive, resulting in poor health outcomes such as unsuppressed viral load and higher AIDS-related death among men [ 5 , 6 , 12 , 17 ]. The recent Test-as-Prevention (TasP) trial conducted in rural South Africa had no significant effect [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Men (especially young men) have been consistently missing from the cascade of HIV care, leading to poor health outcomes in men and ongoing transmission of HIV in young women. Although these men may not be missing for the same reasons across the cascade and may need different interventions, early work has shown similar trends in men’s low uptake of HIV care services and suggested that the social costs of testing and accessing care are extremely high for men, particularly in South Africa [ 3 , 5 , 6 , 12 , 17 , 18 ]. Interventions and data collection have hitherto, by and large, focused on men in relation to HIV prevention in women and have not approached the problem through the male lens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3), including for those who would otherwise not engage in testing. [13][14][15][16] Service level Digital health enables remote service delivery, including the provision of health and service information online, the ability for a service user to book appointments and access test kits, and to provide appointment reminders, test results and other information using SMS, email and web applications. Many DHIs, for example, online postal self-sampling services in England, have been developed to provide access to care to those with the least needs remotely in order to free up capacity to see more complex cases in clinic-based service.…”
Section: Individual Levelmentioning
confidence: 99%
“…Drivers of risk and barriers to effective uptake of multi-level HIV prevention for adolescents and young adults in rural KZN drawn from survey data (n = 4918) and studies conducted 2016-2018[1,6,8,37,40,[43][44][45][46][47][48][49][51][52][53][54][55][56] …”
mentioning
confidence: 99%